2019
DOI: 10.1002/stco.201900029
|View full text |Cite
|
Sign up to set email alerts
|

Design of simply supported hot‐rolled steelshort‐to‐intermediate angle columns

Abstract: Selected, extended paper from the SDSS 2019 special session ECCS/TC8 – Structural Stability This work reports on the results of an ongoing investigation of the direct strength method (DSM) design of hot‐rolled steel equal‐leg angle columns with pinned (spherically hinged) supports and short‐to‐intermediate lengths, i.e. buckling in flexural‐torsional modes. It extends the scope of similar studies involving cold‐formed steel angle columns with the same characteristics (but higher leg width‐to‐thickness ratios)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…They concern 84 specimens with measured cross-section dimensions such that 18.5 ≥ b/t ≥ 12.5 and whose material/steel properties and failure loads can be found in [16]. The parametric studies reported in [16][17][18] concern columns with (i) cross-section dimensions such that 20 ≥ b/t ≥ 10 and (ii) lengths and yield stresses (elasticperfectly plastic material model) selected to ensure buckling in FT modes and covering a wide slenderness range − the yield stress interval is 700 ≥ fy ≥ 150 MPa. Sets of 108 F, 108 PC and 144 PS columns were analysed, all containing 3-point residual stress distributions ( Fig.…”
Section: Experimental and Numerical Failure Load Datamentioning
confidence: 99%
See 4 more Smart Citations
“…They concern 84 specimens with measured cross-section dimensions such that 18.5 ≥ b/t ≥ 12.5 and whose material/steel properties and failure loads can be found in [16]. The parametric studies reported in [16][17][18] concern columns with (i) cross-section dimensions such that 20 ≥ b/t ≥ 10 and (ii) lengths and yield stresses (elasticperfectly plastic material model) selected to ensure buckling in FT modes and covering a wide slenderness range − the yield stress interval is 700 ≥ fy ≥ 150 MPa. Sets of 108 F, 108 PC and 144 PS columns were analysed, all containing 3-point residual stress distributions ( Fig.…”
Section: Experimental and Numerical Failure Load Datamentioning
confidence: 99%
“…In order to assess the performance/merits of the above DSM-based design approaches in estimating hotrolled steel angle column failure loads, one considers next the predictions (Pnfte) concerning the whole set of F (numerical), PC (numerical) and PS (experimental and numerical) failure loads gathered in Section 3 − the corresponding failure-to-predicted strength ratios Pu /Pnfte can be found in tables presented in [16][17][18]. Moreover, the failure load prediction quality is also assessed through the determination of the LRFD resistance factor (φc) associated with the estimates provided by the proposed DSM design approaches.…”
Section: Merit Assessment Of the Dsm-based Design Approach For Hot-romentioning
confidence: 99%
See 3 more Smart Citations